Materials Selection and Design - Maleque, Md Abdul; Salit, Mohd Sapuan; SpringerLink (Online service) (Singapore : Springer Singapore : Imprint: Springer, 2013)
This book presents topics on the basics of materials selection and design which will give a better understanding on the selection methods and then find suitable materials for the applications. This book draws the simple and straightforward quantitative methods followed by knowledge-based expert system approach with real and tangible case studies to show how undergraduate or post-graduate students or engineers can apply their knowledge on materials selection and design. Topics discussed in this book contain special features such as illustration, tables, and tutorial questions for easy understanding. A few published books or documents are available, hence this book will be very useful for those who use (or want to use) materials selection approach without the advantages of having had comprehensive knowledge or expertise in this materials$1 (Bworld.s
Overview of Materials Selection and Design -- Materials Performance -- Design Phases -- Materials Properties and Design -- Materials Selection Process -- Knowledge-base Expert System in Materials Selection.
Keywords: Engineering design; Structural control (Engineering).; Surfaces (Physics).; Materials Science; Characterization and Evaluation of Materials; Engineering Design; Operating Procedures, Materials Treatment